Digital watermarking scheme for QR code security - Tan Lei Lei, Joanna; Liew, Siau-Chuin (2021)
QR code image digital watermarking with tamper localization and exact recovery using multi-level authentication. Automated calculation of watermark detection result and better visualization of tamper detection and QR code image recovery results.